Brain Metabolic Profile in Presymptomatic GRN Carriers Throughout a 5-Year Follow-up. (24th January 2023) - Saracino, Dario; Sellami, Leila; Boniface, Hugo; Houot, Marion; Pélégrini-Issac, Mélanie; Funkiewiez, Aurélie; Rinaldi, Daisy; Locatelli, Maxime; Azuar, Carole; Causse-Lemercier, Valérie; Jaillard, Alice; Pasquier, Florence; et al.
Abstract : Background and Objectives: GRN variants are a frequent cause of familial frontotemporal dementia (FTD). Monitoring disease progression in asymptomatic carriers of genetic variants is a major challenge in delivering preventative therapies before clinical onset. This study aimed to assess the usefulness of fluorodeoxyglucose (FDG)–PET in identifying metabolic changes in presymptomatic GRN carriers (PS- GRN +) and to trace their longitudinal progression. Methods: Participants were longitudinally evaluated over 5 years in a prospective cohort study focused on GRN disease (Predict-PGRN). They underwent cognitive/behavioral assessment, plasma neurofilament measurement, brain MRI, and FDG-PET. Voxel-wise comparisons of structural and metabolic imaging data between 2 groups were performed for each time point. Longitudinal PET changes were evaluated with voxel-wise comparisons and the metabolic percent annual changes method. The association of regional brain metabolism with plasma neurofilament and cognitive changes was analyzed. Results: Among the 80 individuals enrolled in the study, 58 (27 PS- GRN + and 31 noncarriers) were included in the analyses. Cross-sectional comparisons between PS- GRN + and controls found a significant hypometabolism in the left superior temporal sulcus (STS) region (encompassing the middle and superior temporal gyri), approximately 15 years before the expected disease onset, without significant cortical atrophy. The longitudinal metabolic decline over the following 5 years peaked around the right STS in carriers ( p < 0.001), without significantly greater volume loss compared with that in controls. Their estimated annualized metabolic decrease (−1.37%) was higher than that in controls (−0.21%, p = 0.004). Lower glucose uptake was associated with higher neurofilament increase ( p = 0.003) and lower frontal cognitive scores ( p = 0.014) in PS- GRN +. Discussion: This study detected brain metabolic changes in the STS region, preceding structural and cognitive alterations, thus contributing to the characterization of the pathochronology of preclinical GRN disease. Owing to the STS involvement in the perception of facially communicated cues, it is likely that its dysfunction contributes to social cognition deficits characterizing FTD. Overall, our study highlights brain metabolic changes as an early disease-tracking biomarker and proposes annualized percent decrease as a metric to monitor therapeutic response in forthcoming trials.